2017
DOI: 10.1152/jn.00381.2017
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation inhibits sympathetic action potential recruitment even during severe chemoreflex stress

Abstract: The current study demonstrates that the sympathetic neural recruitment patterns observed during chemoreflex activation induced by rebreathing or apnea are restrained and/or inhibited by the act of ventilation per se, despite similar, or even greater, levels of severe chemoreflex stress. Therefore, ventilation modulates not only the timing of sympathetic bursts but also the within-burst axonal recruitment normally observed during progressive chemoreflex stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
20
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 43 publications
9
20
3
Order By: Relevance
“…Therefore, displaying AP latency as a function of AP cluster size indicates the shorter latency of larger AP clusters . Of note, repeated observations that the larger APs also express faster conduction velocity (Badrov et al 2015(Badrov et al , 2017 discount the potential problem that they simply represent axons that lie closer to the recording electrode.…”
Section: )mentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, displaying AP latency as a function of AP cluster size indicates the shorter latency of larger AP clusters . Of note, repeated observations that the larger APs also express faster conduction velocity (Badrov et al 2015(Badrov et al , 2017 discount the potential problem that they simply represent axons that lie closer to the recording electrode.…”
Section: )mentioning
confidence: 95%
“…Concurrently, new clusters of larger APs emerged, representing a recruitment response. A second pattern observed was that the recruitment of new large APs progressed with the severity of the stress, be it apneas (Badrov et al 2017), isometric exercise (Badrov et al 2016b), or baroreceptor unloading (Badrov et al 2015;Salmanpour et al 2011a). Importantly, the appearance of larger APs observed during fatiguing handgrip persisted during a period of postexercise forearm ischemia highlighting the important role of peripheral muscle metaboreceptors in the recruitment of the latent AP pool.…”
Section: )mentioning
confidence: 95%
“…However, the former study did not show the influence of dynamic ventilation on MSNA at two matched chemical stressors. More recently, Badrov et al (2017) also demonstrated lower action potential recruitment when they matched a similar rebreathing protocol to maximal BHs at functional residual capacity within elite BH divers. Within our own findings, when stress is matched between rebreathing and our BH (end-inspiratory), rebreathing exhibited a markedly blunted MSNA response.…”
Section: Msna Response To Dynamic Ventilation Versus Static Lung Volumentioning
confidence: 96%
“…Still, muscle sympathetic nerve activity (burst frequency and amplitude) markedly increases during a maximal dry static breath hold by an astounding ∼2000% from baseline (Heusser et al., ; Steinback et al., ). In part because the increase in sympathetic nerve activity is dependent on the duration of breath hold, the primary stimulus for the large sympathetic response during a maximal dry breath hold was initially suggested to result from chemostress (Heusser et al., ); however, it is more likely that mounting pulmonary nerve activity is largely responsible (Badrov et al., ). Thus, ventilation per se partly restrains sympathetic axonal recruitment even during extreme chemoreflex stress (Badrov et al., ).…”
Section: Cardiovascular Regulation and The Dive Responsementioning
confidence: 99%
“…In part because the increase in sympathetic nerve activity is dependent on the duration of breath hold, the primary stimulus for the large sympathetic response during a maximal dry breath hold was initially suggested to result from chemostress (Heusser et al., ); however, it is more likely that mounting pulmonary nerve activity is largely responsible (Badrov et al., ). Thus, ventilation per se partly restrains sympathetic axonal recruitment even during extreme chemoreflex stress (Badrov et al., ). Moreover, breath holds performed at different lung volumes will dramatically impact muscle sympathetic nervous activity (Breskovic, Steinback, Salmanpour, Shoemaker, & Dujic, ; Dujic et al., ; Heusser et al., , ; Steinback, Breskovic, Banic, Dujic, & Shoemaker, ; Steinback et al., ) and central blood flow distribution (Stembridge et al., ).…”
Section: Cardiovascular Regulation and The Dive Responsementioning
confidence: 99%